Workload and Work-Life Balance - Andrie Firmansyah (International Journal of Economics and Management Research, 2023)
Work-life balance is a concern that employers with high workloads must take note of. This study seeks to ascertain the state of the workload and work-life balance at PT. Wings Abadi Airlines. Study This qualitative study investigates the field conditions using data gathered from captain and company employee interviews to determine respondents' perspectives of the current workload environment and work-life balance take off. The findings indicated that Wings Air employees experience high levels of workload, but the staff members of the company make an effort to work in a professional manner, maintain a healthy work-life balance, and avoid interpersonal conflict while in the air.